2021
DOI: 10.1027/0227-5910/a000712
|View full text |Cite
|
Sign up to set email alerts
|

State Anhedonia and Suicidal Ideation in Adolescents

Abstract: Abstract. Background: Recent work suggests that state anhedonia and its social aspect of loss of interest in people was an important predictor of suicidal ideation in adults. Aim: The current study investigated the relationship between state anhedonia, trait anhedonia, suicidal ideation, and suicide attempts in adolescents. Method: State anhedonia was assessed using the anhedonia subscale from the Child Mood and Feelings Questionnaire, while trait social anhedonia was assessed using the Adolescent Anticipatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…Indeed, lifelong anhedonia and recent changes in anhedonia were present in 26.0% and 41.7% of the major depressed subjects in our sample, respectively. Additionally, similar to other specific subpopulations [16,17,31,32], we demonstrated that unlike lifelong anhedonia, only recent changes in anhedonia were associated with a higher risk of suicidal ideations in major depressed subjects. Pathophysiologically, several elements could help to better understand this high prevalence of recent changes in anhedonia and their implication in the development of suicidal ideations in major depressed subjects.…”
Section: Discussionsupporting
confidence: 85%
“…Indeed, lifelong anhedonia and recent changes in anhedonia were present in 26.0% and 41.7% of the major depressed subjects in our sample, respectively. Additionally, similar to other specific subpopulations [16,17,31,32], we demonstrated that unlike lifelong anhedonia, only recent changes in anhedonia were associated with a higher risk of suicidal ideations in major depressed subjects. Pathophysiologically, several elements could help to better understand this high prevalence of recent changes in anhedonia and their implication in the development of suicidal ideations in major depressed subjects.…”
Section: Discussionsupporting
confidence: 85%
“…However, Winer et al [ 3 ] have suggested that the social component of recent change of anhedonia, as rated by the 12th item « Loss of interest » of the BDI-II or by the SLIPS, was the most predictive component of suicidal ideation. This suggestion has been confirmed in several studies that included high school students, university students and psychiatric patients [ 3 , 7 , 8 , 10 , 21 , 22 ]. Two studies on physicians and medical students did not report such an association [ 9 , 23 ].…”
Section: Introductionmentioning
confidence: 53%
“…In depression, the hypothesis has not been tested as two studies explored either psychiatric patients [ 3 ] or a mixed sample of healthy subjects and major depressives [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The level of suicidal ideation of depressed patients with generalized anxiety disorder was higher than that of patients with depression alone [ 17 , 18 ]. Some specific symptoms of anxiety and depression have been found to be related to suicidal ideation, such as worry and anhedonia [ 19 , 20 ], however, considering multiple factors comprehensively may be more meaningful for predicting suicidal ideation [ 1 ]. There are complex psychopathological pathways between anxiety and suicidal ideation and between depression and suicidal ideation that still need to be further studied.…”
Section: Introductionmentioning
confidence: 99%